Analysis of One-Bond Se-Se Nuclear Couplings in Diselenides and 1, 2-Diselenoles on the Basis of Molecular Orbital Theory: Torsional Angular Dependence, Electron Density Influence, and Origin in J1(Se, Se). (6th August 2009) - Tanioku, Akito; Hayashi, Satoko; Nakanishi, Waro
Abstract : Nuclear couplings for the Se-Se bonds, J 1 ( Se, Se ), are analyzed on the basis of the molecular orbital (MO) theory. The values are calculated by employing the tripleζ basis sets of the Slater type at the DFT level.J 1 ( Se, Se ) are calculated modeled by MeSeSeMe (1a ), which shows the typical torsional angular dependence onϕ ( C Me SeSeC Me ) . The dependence explains well the observedJ 1 ( Se, Se ) obsd of small values (≤ 64 Hz) forRSeSeR ′ (1 ) (simple derivatives of1a ) and large values (330–380 Hz) observed for 4-substituted naphto[1, 8-c, d ]-1, 2-diselenoles (2 ) which correspond to symperiplanar diselenides.J 1 (Se, Se :2 ) becomes larger as the electron density on Se increases. The paramagnetic spin-orbit terms contribute predominantly. The contributions are evaluated separately from each MO( ψ i ) and eachψ i → ψ a transition, whereψ i andψ a are occupied and unoccupied MO's, respectively. The separate evaluation enables us to recognize and visualize the origin and the mechanism of the couplings.